Evaluation of an Antibiotic Cocktail for Fecal Microbiota Transplantation in Mouse - Tan, Jijun; Gong, Jiatai; Liu, Fengcheng; Li, Baizhen; Li, Zhanfeng; You, Jiaming; He, Jianhua; Wu, Shusong (Frontiers in Nutrition, 2022)
Objective: To evaluate the effect of an antibiotic cocktail on gut microbiota, and provide a reference for establishing an available mouse model for fecal microbiota transplantation (FMT) of specific microbes. Design: C57BL/6J mice (n=24) had free access to an antibiotic cocktail containing vancomycin (0.5 g/L), ampicillin (1 g/L), neomycin (1 g/L) and metronidazole (1 g/L) in drinking water for 3 weeks. Fecal microbiota was characterized by 16S rDNA gene sequencing at the beginning, 1st week and 3rd week, respectively. The mice were then treated with fecal microbiota from normal mice for 1 week to verify the efficiency of FMT. Results: The diversity of microbiota including chao1, observed species, PD whole tree and shannon index were decreased significantly (P < 0.05) after treated with the antibiotic cocktail for 1 week or 3 weeks. The relative abundance of Bacteroidetes, Actinobacteria and Verrucomicrobia was decreased by 99.94%, 92.09% and 100%, respectively, while Firmicutes dominated the microbiota at the phylum level after 3 weeks treatment. Meanwhile, Lactococcus, a genus belonging to the phylum of Firmicutes dominated the microbiota at the genus level with a relative abundance of 80.63%. Further FMT experiment indicated that the fecal microbiota from the receptor mice had a similar composition with the donor mice after 1 week. Conclusion: The antibiotic cocktail containing vancomycin, ampicillin, neomycin and metronidazole eliminates microbes belong to Bacteroidetes, Actinobacteria and Verrucomicrobia, which can be recovered by FMT in mice.